2022
DOI: 10.1371/journal.pone.0276803
|View full text |Cite|
|
Sign up to set email alerts
|

The Big Five personality traits and the fear of COVID-19 in predicting depression and anxiety among Japanese nurses caring for COVID-19 patients: A cross-sectional study in Wakayama prefecture

Abstract: Recent studies have found a relationship between fear of COVID-19 and mental health problems. Medical workers caring for COVID-19 patients tend to suffer from mental health problems; however, the impact of their personality traits, in the form of mental problems like depression and anxiety in Japan is unclear. In this study, we investigated the risk of nurses’ depression and anxiety, predicted by the fear of COVID-19 and the Big Five personality traits. A total of 417 nurses working in hospitals providing care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 96 publications
(95 reference statements)
2
13
2
Order By: Relevance
“…Because most of the scales had a positive flavor, neuroticism was negatively correlated with virtually all measures but specially with self-esteem, SWLS, optimism (both the aggregate and positive scores of LOT-R), environmental mastery, self-acceptance and SHS. Neuroticism has been associated with a host of different mood and physical disorders (Lahey, 2009), especially depression (Hakulinen et al, 2015;Odachi et al, 2022;Xia et al, 2011); therefore, as expected, neuroticism was positively correlated with CES-D in the current sample. Extraversion, on the other hand, was negatively correlated with CES-D and positively correlated with positive orientation, self-esteem, optimism and scales associated with SWB, i.e., SWLS (Diener et al, 1992;Steel et al, 2008) and SHS (Lauriola & Iani, 2015), as well as with all the PWB dimensions (Kokko et al, 2013), except for autonomy and purpose in life.…”
Section: Psychological Scalessupporting
confidence: 73%
“…Because most of the scales had a positive flavor, neuroticism was negatively correlated with virtually all measures but specially with self-esteem, SWLS, optimism (both the aggregate and positive scores of LOT-R), environmental mastery, self-acceptance and SHS. Neuroticism has been associated with a host of different mood and physical disorders (Lahey, 2009), especially depression (Hakulinen et al, 2015;Odachi et al, 2022;Xia et al, 2011); therefore, as expected, neuroticism was positively correlated with CES-D in the current sample. Extraversion, on the other hand, was negatively correlated with CES-D and positively correlated with positive orientation, self-esteem, optimism and scales associated with SWB, i.e., SWLS (Diener et al, 1992;Steel et al, 2008) and SHS (Lauriola & Iani, 2015), as well as with all the PWB dimensions (Kokko et al, 2013), except for autonomy and purpose in life.…”
Section: Psychological Scalessupporting
confidence: 73%
“…Also, between the fourth and fifth wave in Japan, 417 nurses were surveyed to assess their ability to cope with COVID-19. In this study, extraversion was found to play no role in protecting against depression or anxiety and did not predict better coping [51]. There were no studies found that concentrated on the sixth wave alone when this search was undertaken.…”
Section: Waves 5 and Higher Wavescontrasting
confidence: 53%
“…Symptoms of depression and anxiety were assessed by the Hospital Anxiety and Depression Scale Depression (HADS‐D) and Anxiety (HADS‐A) subscales, respectively 17–19 . The HADS has been validated in healthy populations, 20,21 and used in several previous studies that examined mental health problems among COVID‐19 frontline healthcare workers 7,22–24 . Personality traits of participants were assessed by the Big Five personality traits, 25,26 and fear of COVID‐19 was assessed using the Fear of COVID‐19 Scale 27,28 …”
Section: Methodsmentioning
confidence: 99%
“…[17][18][19] The HADS has been validated in healthy populations, 20,21 and used in several previous studies that examined mental health problems among COVID-19 frontline healthcare workers. 7,[22][23][24] Personality traits of participants were assessed by the Big Five personality traits, 25,26 and fear of COVID-19 was assessed using the Fear of COVID-19 Scale. 27,28 Statistics JMP Pro 14.0 was used for statistical calculation.…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation